2018
DOI: 10.1136/bmjopen-2017-021465
|View full text |Cite
|
Sign up to set email alerts
|

Impact and longevity of measles-associated immune suppression: a matched cohort study using data from the THIN general practice database in the UK

Abstract: ObjectiveTo test the hypothesis that measles infection increases the incidence of non-measles infectious diseases over a prolonged period of time.DesignA population-based matched cohort study.Data sourcesThis study examined children aged 1–15 years in The Health Improvement Network UK general practice medical records database. Participants included 2228 patients diagnosed with measles between 1990 and 2014, which were matched on age, sex, general practitioner practice and calendar year with 19 930 children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 21 publications
4
25
0
2
Order By: Relevance
“…Measles is characterised by fever, cough and a maculopapular skin rash 1 . The disease is associated with a transient immune suppression and increased risk of childhood morbidity and mortality for a period of more than 2 years 2 , 3 , 4 . Paradoxically, measles also induces strong cellular and humoral immune responses that mediate lifelong protection 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Measles is characterised by fever, cough and a maculopapular skin rash 1 . The disease is associated with a transient immune suppression and increased risk of childhood morbidity and mortality for a period of more than 2 years 2 , 3 , 4 . Paradoxically, measles also induces strong cellular and humoral immune responses that mediate lifelong protection 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Measles-induced lymphocytopenia as well as its grade, possibly has a role either as a disease severity biomarker or as a predisposing factor for short- and long-term infectious complications. There is growing evidence that measles infection induces immunosuppression; a recent study in measles-infected children found significantly higher rates of hospitalization (during the first month), of non-measles infections and of antimicrobial prescriptions up to 5 years post-measles, compared to children without measles [ 17 ]. Mina et al showed that measles infection, but not MMR vaccination, reduces the humoral immune memory against numerous viruses in children [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in the Netherlands has confirmed that measles virus infection can reduce pre-existing protective antibodies [ 34 ]. The association of measles infection with increased morbidity and mortality due to non-measles infectious disease has been shown in populations of children from wealthy countries, and this increased mortality rate appears to last for 2–3 years after the infection [ 35 , 36 ].…”
Section: Indirect Benefits Of Vaccines and Vaccinationmentioning
confidence: 99%